Knowledge And Awareness About The Risk Of HIV/AIDS Among Truck Drivers Of A Selected Area - Sadhya, G; Islam, AKMS; Islam, R; Ahmed, NU; Rahman, M (Faridpur Medical College Journal, 2011)
This cross- sectional study was conducted among the truck drivers at Daulatdia Ghat, Goalanda, Rajbari district. The objective of this study was to find out the knowledge and awareness about the risk of HIV/AIDS transmission among the truck drivers .Out of 226 respondents, 37.3% were within the age group 25 to 35 years. Most of the respondents (74%) were married and 44% were educated up to primary level. Half of the respondents (50%) had monthly income from taka 10,000 to taka 15,000 per month. From this study, it was found that 97% respondents had heard the name of HIV/AIDS, 61.8% had known about HIV/AIDS from media and newspaper. In respect of the route of HIV transmission, 39.8% of respondents thought that HIV is transmitted by sexual activities and 58.7% thought the disease is transmitted by syringe, transfusion. About 47.8% respondents thought that HIV can be detected from blood and 76% knew the fate of HIV/AIDS is death. Majority (82.5%) of the respondents obtained correct knowledge about HIV/AIDS transmission and 13.2% of them knew the place where test of HIV can be done. Key words: Knowledge; HIV/AIDS; Risk; Truck drivers DOI: 10.3329/fmcj.v5i2.6820 Faridpur Med. Coll. J. 2010;5(2):46-49